2017
DOI: 10.1101/105270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Group-level progressive alterations in brain connectivity patterns revealed by diffusion-tensor brain networks across severity stages in Alzheimer’s disease

Abstract: Abstract. Alzheimer's disease (AD) is a chronically progressive neurodegenerative disease highly correlated to aging. Whether AD originates by targeting a localized brain area and propagates to the rest of the brain across disease-severity progression is a question with an unknown answer. Here, we aim to provide an answer to this question at the group-level by looking at differences in diffusiontensor brain networks. In particular, making use of data from Alzheimer's Disease Neuroimaging Initiative (ADNI), fou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Early pathogenic crosstalk between CSF Ab42 and tau may induce intracellular NFT deposition causing neuronal death, atrophy, and cognitive changes [38]. Network analyses suggest a specific and progressive disconnection of functional and anatomical networks over the course of the disease [103][104][105][106]. Interestingly, some evidence suggests that subtle cognitive impairment occurs before detectable atrophy [164], and this is an area yet to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early pathogenic crosstalk between CSF Ab42 and tau may induce intracellular NFT deposition causing neuronal death, atrophy, and cognitive changes [38]. Network analyses suggest a specific and progressive disconnection of functional and anatomical networks over the course of the disease [103][104][105][106]. Interestingly, some evidence suggests that subtle cognitive impairment occurs before detectable atrophy [164], and this is an area yet to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…The view of AD as a disconnection syndrome in which brain regions become successively disconnected both structurally and functionally during the course of AD disease progression is now well established with considerable evidence to support it [7]. Progressive alterations in brain functional networks were reported in a study, which used diffusion tensor imaging of 20 modules shown to have the best correspondence between structural and functional network modules [103]. Compared to CN participants, early MCI participants showed no significant differences in functional connectivity, but late MCI participants differed in the con-nectivity of a memory function subnetwork (module 18), and AD participants had widespread disconnection affecting the same memory subnetwork in addition to the DMN, medial visual network, sensorimotor network, subcortical networks, and others (Fig.…”
Section: Role Of Network In Admentioning
confidence: 99%
See 2 more Smart Citations
“…An fMRI study also demonstrated significant alteration of connectivity patterns in a memory-related subnetwork, including part of the HP, amygdala, fusiform gyrus, ITG, and MTG at the late stage of MCI and the deficits propagated to the rest of the brain as disease progressed. [23] Granger causality analysis revealed that directed FC between the HP and the temporal lobe, frontal lobe, and cingulate cortex were significantly changed in MCI [24]. On the other hand, increased spontaneous brain activities and FC have also been revealed in the frontal and temporal cortex in aMCI patients [25,26].…”
Section: Discussionmentioning
confidence: 94%